Neonatal Adverse Outcomes of Induction and Expectant Management in Fetal Growth Restriction: A Systematic Review and Meta-Analysis - Li, Ting; Wang, Yixiao; Miao, Zhijing; Lin, Yu; Yu, Xiang; Xie, Kaipeng; Ding, Hongjuan (Frontiers in Pediatrics, 2020)
Background and Objective: Fetal growth restriction (FGR) is a pathological condition in which the fetus cannot reach its expected growth potential. When it is diagnosed as a suspected FGR, it remains an unsolved problem whether to direct induction or continue expectant management. To effectively reduce the incidence of neonatal adverse outcomes, we aimed to evaluate whether either method was associated with a lower incidence of neonatal adverse outcomes. Methods: We searched the relevant literature through the PubMed, Web of Science, and Cochrane Library from inception to January 10, 2020. We defined induction as the experimental group and expectant management as the control group. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using random-effects models owing to heterogeneity. Furthermore, we conducted a sensitivity analysis to explore the robustness of the included literature. We used the Newcastle-Ottawa scale (NOS) to evaluate the quality of the available studies. We applied the funnel plot to describe the publication bias. Additionally, subgroup analysis based on the study method, sample size, area, NOS score, Apgar score <7 at 5 min, definition of suspected FGR, severity, and neonatal adverse outcomes were performed to further evaluate the differences between the induction and expectant management. Results: Our study included a total of eight articles with 6,706 patients, which consisted of four randomized controlled trials (RCTs), three retrospective cohort studies, and one prospective cohort study. The total pooled OR and 95% CI between the induction group and the expected management group was 1.38 (95% CI, 0.84–2.28) in the random model. The heterogeneity was I2 = 84%, P < 0.01. The sensitivity analysis showed that the neonatal adverse outcomes of induction vs. expectant management still presented similar outcomes after omitting of any one of these studies. The funnel plot and linear regression equation showed that there was no publication bias in our study (P = 0.75). Subgroup analysis showed that induction increased the neonatal adverse outcome risks of hypoglycemia and respiratory insufficiency (ORneonatal hypoglycaemia = 8.76, 95% CI: 2.57–29.90; ORrespiratory insufficiency = 1.74, 95% CI: 1.35–2.24, respectively). However, no significant differences were observed based on the other subgroups (all P > 0.05). Conclusion: Regardless of induction or expectant management of a suspected FGR, the neonatal adverse outcomes showed no obvious differences. More studies should be conducted and confounding factors should be taken into consideration to elucidate the differential outcomes of the two approaches for suspected FGR.